A modified graphitic carbon nitride (MCN)/Fe3O4 composite as a super electromagnetic wave absorber. Issue 41 (18th October 2021) - Zhu, Xiaoyu; Qiu, Hongfang; Chen, Ping
Abstract : The nitrogen content of g-C3 N4 was reduced by magnesium thermal reduction to obtain porous C (MCN), and MCN was combined with Fe3 O4 particles by decomposition of ferric acetylacetonate. Abstract : Several composites of modified graphitic carbon nitride (MCN) and Fe3 O4 particles were obtained through pyrolysing MCN/iron acetylacetone (Fe(acac)3 ) at different temperatures to form electromagnetic wave (EWM) absorbers. By decreasing the nitrogen content of g-C3 N4 and introducing Fe3 O4 particles, the EMW absorption ability of the g-C3 N4 derivatives (MCN/Fe3 O4 ) improved remarkably. For MCN/Fe3 O4 -500 with 6 wt% filling, the minimum reflection loss (RLmin ) reached −73.93 dB at a thickness of 3.4 mm and the effective absorption bandwidth (EAB) was as high as 5.44 GHz at a thickness of 1.9 mm. Additionally, the mass ratio of MCN and Fe3 O4 and the EMW absorption mechanism of MCN/Fe3 O4 -500 were also discussed. This study provides a new approach for the preparation of high-efficiency EMW absorbers by modification of g-C3 N4 .